Resin foam

By developing resin foams with specific compression loads and compression stress retention rates and imparting bubble structures to them, it is solved that in the prior art, it is difficult for resin foams to achieve high impact absorption and prevent display in thin electronic devices at the same time. The problem of uniformity achieves the effect of providing efficient impact absorption and display stability in electronic devices.

CN114761473BActive Publication Date: 2025-02-25NITTO DENKO CORP
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202080081924.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-25
Filing Date
2020-11-25
Publication Date
2025-02-25
Estimated Expiration
2040-11-25

AI Technical Summary

Technical Problem

The prior art is difficult to provide a resin foam in a thinner electronic device that has both high impact absorption and prevents uneven display caused by pressing.

Method used

A resin foam has been developed, with a 50% compression load between 5N/cm2 and 30N/cm2. The compression stress retention rate after 6 hours and the compression stress retention rate after 12 hours both reach more than 50%, and has Bubble structure.

Benefits of technology

It is achieved to provide high impact absorption in thin electronic devices, while preventing display unevenness caused by pressing, ensuring display stability of the liquid crystal display device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114761473B_ABST
    Figure CN114761473B_ABST
Patent Text Reader

Abstract

The present invention provides a resin foam which is thin, has excellent impact absorption, and can prevent display unevenness caused by pressing when applied to an image display device. The 50% compression load of the resin foam of the present invention is 5 N / cm 2 ~30N / cm 2 , the compressive stress retention rate after 6 hours is 50% or more, the compressive stress retention rate after 12 hours is 50% or more, and has a bubble structure. In one embodiment, the 50% compressive load of the resin foam is 30N / cm 2 In one embodiment, the resin foam has a compression modulus of 200 kPa or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin foam. Background Art

[0002] Resin foams are often used as cushioning materials for protecting screens and substrates of electronic devices. In recent years, in response to the trend of thinning of electronic devices, cushioning materials are required to exhibit high impact absorption even when arranged at narrow gaps.

[0003] In addition, in touch panel LCD devices such as smartphones and mobile terminals, the orientation of liquid crystal molecules in the LCD panel may be disturbed, resulting in uneven display (a wavy bleeding pattern; so-called pulling pattern), mainly due to the depression caused by the user pressing the screen. This phenomenon has become a particular problem with the trend of thinning devices in recent years.

[0004] Reference document 1 discloses a foam sheet with good impact absorption and anti-stretching pattern characteristics that can make the generated stretching pattern disappear at an early stage. However, even with this technology, it is difficult to prevent the generation of the stretching pattern itself. In addition, patent document 2 discloses a foam body that improves stress dispersion and is less likely to cause uneven display of the panel, but there is no disclosure about impact absorption.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2007-016070

[0008] Patent Document 2: International Publication No. WO12 / 133288 Summary of the invention

[0009] Problems to be solved by the invention

[0010] An object of the present invention is to provide a resin foam which is thin, has excellent impact absorption, and can prevent display unevenness due to pressure when used in an image display device.

[0011] Solutions to the problem

[0012] The 50% compression load of the resin foam of the present invention is 5 N / cm 2 ~30N / cm 2 , the compressive stress retention rate after 6 hours is more than 50%, the compressive stress retention rate after 12 hours is more than 50%, and it has a bubble structure.

[0013] In one embodiment, the 50% compression load of the resin foam is 10 N / cm2 ~30N / cm 2 .

[0014] In one embodiment, the resin foam has a compression modulus of 200 kPa or more.

[0015] In one embodiment, the resin foam has a non-foamed bending stress of 5 MPa or more.

[0016] In one embodiment, the thickness change rate of the resin foam due to repeated compression is 10% or less.

[0017] In one embodiment, the apparent density of the resin foam is 0.02 g / cm 3 ~0.50g / cm 3 .

[0018] In one embodiment, the thickness recovery rate of the resin foam is 75% or more.

[0019] In one embodiment, the aspect ratio of cells included in the resin foam is 1.5 or more.

[0020] In one embodiment, the resin foam has an average cell diameter of 10 μm to 200 μm.

[0021] In one embodiment, the resin foam has a cell ratio of 30% or more.

[0022] In one embodiment, the coefficient of variation of the cell diameter of the resin foam is 0.5 or less.

[0023] In one embodiment, the thickness of the cell walls of the resin foam is 0.1 μm to 10 μm.

[0024] In one embodiment, the resin foam includes a polyolefin resin.

[0025] In one embodiment, the polyolefin resin is a mixture of a polyolefin other than a polyolefin elastomer and a polyolefin elastomer.

[0026] In one embodiment, the resin foam has a heat-fusible layer on one side or both sides.

[0027] According to another aspect of the present invention, there is provided a foam member including a resin foam layer and an adhesive layer disposed on at least one side of the resin foam layer, wherein the resin foam layer is the above-mentioned resin foam.

[0028] Effects of the Invention

[0029] A resin foam can be provided which is thin, has excellent impact absorption, and can prevent display unevenness caused by pressing when applied to an image display device. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is a schematic cross-sectional view of a foam material according to one embodiment of the present invention.

[0031] Figure 2 It is a cross-sectional schematic diagram of a stress relaxation testing machine.

[0032] Explanation of symbols

[0033] 100 Foam components

[0034] 10 Resin foam layer

[0035] 20 Adhesive layer

[0036] 1000 Stress Relaxation Testing Machine

[0037] A Iron support

[0038] 200 Polycarbonate Sheet

[0039] 300 Stress Testing Film

[0040] 400 Resin foam structure

[0041] 500 Double-sided adhesive tape

[0042] 600 Spacer

[0043] 700 ABS board

[0044] 800 Iron Ball DETAILED DESCRIPTION

[0045] A. Resin foam

[0046] The 50% compression load of the resin foam of the present invention is 5 N / cm 2 ~30N / cm 2 , the compression stress retention rate after 6 hours is 50% or more, and the compression stress retention rate after 12 hours is 50% or more. The resin foam of the present invention has a bubble structure (pore structure). As the bubble structure (pore structure), there can be listed an independent bubble structure, a continuous bubble structure, a semi-continuous semi-independent bubble structure (a bubble structure in which an independent bubble structure and a continuous bubble structure are mixed), etc. The bubble structure of the resin foam is preferably a continuous bubble structure, or a semi-continuous semi-independent bubble structure, and more preferably a semi-continuous semi-independent bubble structure. The resin foam of the present invention is obtained by foaming a resin composition. The above-mentioned resin composition is a composition containing at least a resin constituting a resin foam.

[0047] As described above, the 50% compression load of the resin foam of the present invention is 5 N / cm 2 ~30N / cm 2 . If it is within such a range, it is possible to obtain a resin foam having moderate hardness, which is not easily compressed and deformed even when subjected to high impact force, and has excellent impact absorption. In addition, it is possible to obtain a resin foam that can moderately suppress the rebound force when applied to a gap (especially a narrow gap) and can prevent adverse effects on surrounding components. In addition, if the 50% compression load is within the above range, it is possible to obtain a resin foam that can prevent uneven display caused by pressing when applied to an image display device, for example, can prevent color unevenness caused by the disorder of liquid crystal orientation when a touch operation is performed on a liquid crystal display device. 50% compression load is less than 5N / cm 2 When the compression deformation is less likely to occur, there is a concern that the display unevenness caused by pressing when applied to an image display device cannot be prevented. The 50% compression load of the resin foam is preferably 7N / cm 2 ~30N / cm 2 , more preferably 10N / cm 2 ~30N / cm 2 , more preferably 10N / cm 2 ~25N / cm 2 , particularly preferably 10N / cm 2 ~20N / cm 2 If it is within such a range, the above-mentioned effect becomes remarkable.

[0048] As described above, the compressive stress retention rate of the resin foam of the present invention after 6 hours is 50% or more. If it is within such a range, a resin foam that is not easily deformed and can be ideally restored even if deformed can be obtained. Such a resin foam can prevent uneven display caused by pressing when applied to an image display device, for example, it can prevent color unevenness caused by the disorder of liquid crystal orientation when a touch operation is performed on a liquid crystal display device. The compressive stress retention rate of the resin foam after 6 hours is preferably 60% or more, more preferably 70% or more, and further preferably 80% or more. If it is within such a range, the above effect becomes significant. The upper limit of the compressive stress retention rate after 6 hours is, for example, 95% (preferably 98%). According to the compressive stress (N1) when a 30mm×30mm test piece is just compressed to a compression rate of 50% at a compression rate of 10mm / min, and the compressive stress (N2) after 50% compression for 6 hours, the compressive stress retention rate after 6 hours is calculated by the formula N2 / N1×100.

[0049] As described above, the compressive stress retention rate of the resin foam of the present invention after 12 hours is 50% or more. If it is within such a range, a resin foam that is not easily deformed and can be ideally restored even if deformed can be obtained. Such a resin foam can prevent uneven display caused by pressing when applied to an image display device, for example, it can prevent color unevenness caused by the disorder of liquid crystal orientation when a touch operation is performed on a liquid crystal display device. The compressive stress retention rate of the resin foam after 12 hours is preferably 60% or more, more preferably 70% or more, and further preferably 80% or more. If it is within such a range, the above effect becomes significant. The upper limit of the compressive stress retention rate after 12 hours is, for example, 95% (preferably 98%). According to the compressive stress (N1) when a 30mm×30mm test piece is just compressed to a compression rate of 50% at a compression rate of 10mm / min, and the compressive stress (N2) after 50% compression for 12 hours, the compressive stress retention rate after 12 hours is calculated by the formula N2 / N1×100.

[0050] The resin foam of the present invention has the following characteristics: by setting the 50% compression load and the compression stress retention rate to the above range, the resin foam has a given hardness, is not easily deformed, and is easy to recover even if deformed. Such a resin foam has excellent impact absorption and can prevent color unevenness caused by the disorder of liquid crystal orientation when the liquid crystal display device is touched.

[0051] The apparent density of the resin foam of the present invention is preferably 0.02 g / cm 3 ~0.50g / cm 3 If it is within such a range, a resin foam having excellent flexibility and stress dispersion can be obtained. The apparent density of the resin foam of the present invention is more preferably 0.04 g / cm 3 ~0.4g / cm 3 , more preferably 0.06 g / cm 3 ~0.3g / cm 3 , and more preferably 0.08 g / cm 3 ~0.25g / cm 3 , particularly preferably 0.1 g / cm 3 ~0.2g / cm 3 , most preferably 0.13g / cm 3 ~0.2g / cm 3 If it is within such a range, the above-mentioned effect becomes remarkable. The method for measuring the apparent density will be described later.

[0052] The 25% compression load of the resin foam is preferably 3 N / cm 2If it is within this range, the effect of the present invention described above becomes significant. The 25% compression load of the resin foam is preferably 3.2 N / cm 2 More preferably, 3.5 N / cm 2 More preferably, 4N / cm 2 The upper limit of the 25% compression load of the resin foam is, for example, 10 N / cm 2 (Preferably 20N / cm 2 ) The 25% compression load is measured in accordance with the method for measuring the compression hardness of a foam described in JIS K 6767.

[0053] The compression modulus of the resin foam is preferably 200 kPa or more. If it is within this range, a resin foam that is not easily deformed by compression and is not easily broken even when subjected to a high impact force can be obtained. The compression modulus of the resin foam is preferably 220 kPa or more, more preferably 250 kPa or more, and further preferably 300 kPa or more. If it is within this range, the above effect becomes significant. The upper limit of the compression modulus of the resin foam is preferably 1000 kPa, more preferably 800 kPa, and further preferably 600 kPa. Based on the compression test item of JIS K 6767, the compression rate (%) and compression rebound force (kPa) of the resin foam are measured, and the compression rebound force F (5%) at a compression rate of 5% and the compression rebound force F (15%) at a compression rate of 15% are read respectively. The compression modulus of the resin foam is calculated based on F (5%) and F (15%) and by the formula (F (15%) - F (5%)) / (15-5) × 100.

[0054] The elastic strain energy of the resin foam of the present invention when compressed is preferably 10 kPa or more. "Elastic strain energy when compressed" refers to the total amount of compression rebound force when the resin foam is compressed by 10%. Specifically, when the compression rate (%) and compression rebound force (kPa) of the resin foam are measured by a compression test based on JIS K 6767 (test temperature: 23°C, sample size: 10 mm×10 mm, compression speed: 10 mm / min), the "elastic strain energy when compressed" is obtained from a compression ss curve with the x-axis set as the compression rate (%) and the y-axis set as the compression rebound force (kPa). The "elastic strain energy when compressed" is the area of ​​the region defined by the ss curve and the x-axis in the range of compression rate of 0% to 10%. If the elastic strain energy of the resin foam when compressed is within the above range, a resin foam with excellent impact absorption can be obtained. In more detail, when a resin foam having elastic strain energy in the above range is subjected to an impact, the deformation of the resin foam consumes a large amount of energy, so even a strong impact can be well absorbed. The elastic strain energy of the resin foam of the present invention when compressed is more preferably 20 kPa or more, further preferably 30 kPa or more, further preferably 50 kPa or more, further preferably 60 kPa or more, further preferably 80 kPa or more, particularly preferably 100 kPa or more, and most preferably 150 kPa or more. If it is such a range, the above effect becomes significant. The upper limit of the elastic strain energy of the resin foam of the present invention when compressed is, for example, 500 kPa (preferably 800 kPa).

[0055] The non-foamed bending stress of the resin foam of the present invention is preferably 5MPa or more, more preferably 6MPa or more, further preferably 9MPa or more, and particularly preferably 10MPa or more. If it is such a range, it takes a lot of energy to deform the bubble wall (pore wall) of the resin foam, and a resin foam with excellent impact absorption can be obtained. The resin foam of the present invention can achieve an improvement in impact resistance (impact absorption) by moderately reducing the softness that has been valued in cushioning materials in the past and obtaining a balance with other characteristics. Through such a different effect from the past, the resin foam of the present invention that exhibits impact absorption is particularly useful in a structure in which the impact is transmitted in a narrow range (a structure in which the impact is not easy to diffuse in the surface direction), for example, when applied to a flexible component (for example, a component composed of resin). The upper limit of the non-foamed bending stress is preferably 20MPa, more preferably 15MPa. If it is such a range, a resin foam with better softness and stress dispersion can be obtained. "Non-foamed bending stress" refers to the bending stress of a resin molded body a that is restored to a non-foamed state (block) without bubbles by hot pressing the resin foam. The density of the resin molded body a may be the same as the density of the resin molded body b before foaming formed by the resin composition described later. It should be noted that the bending stress of the resin molded body a (non-foamed bending stress of the resin foam) may be the same as that of the resin molded body b. The method for measuring the bending stress will be described later.

[0056] The impact absorption rate of the resin foam is preferably 25% or more, more preferably 30% or more, and even more preferably 35% or more. The impact absorption rate is measured as follows.

[0057] A test body was formed by placing a resin foam, a double-sided tape (Model: No. 5603W, manufactured by Nitto Denko), and a PET film (Model: DIAFOIL MRF75, manufactured by Mitsubishi Plastics) on the impact force sensor in this order. A 66g iron ball was dropped from a height of 50cm above the PET film onto the test body, and the impact force F1 was measured.

[0058] In addition, an iron ball was directly dropped onto the impact force sensor as described above, and the blank impact force F0 was measured.

[0059] · Calculate the impact absorption rate (%) from F1 and F0 using the formula (F0-F1) / F0×100.

[0060] The thickness recovery rate of the resin foam is preferably 75% or more, more preferably 80% or more, and further preferably 85% or more. It should be noted that the thickness recovery rate of the foam layer is defined by the following formula. The thickness recovery rate of the foam layer is a recovery rate measured by applying a load to a certain area of ​​the foam sheet and compressing it, and is different from the so-called depression recovery rate measured by locally applying a load and only causing a part to be depressed.

[0061] Thickness recovery rate (%) = {(thickness 0.5 seconds after release of compression) / (initial thickness)}×100

[0062] Initial thickness: The thickness of the resin foam before a load is applied.

[0063] Thickness 0.5 seconds after releasing the compression: 1000 g / cm 2 The load is maintained for 120 seconds, and the compression is released. The thickness of the resin foam 0.5 seconds after the compression is released is measured.

[0064] The thickness change rate of the resin foam of the present invention caused by repeated compression is preferably 10% or less. If it is within this range, a resin foam that is not easy to break, can prevent gaps with surrounding components when used as a cushioning material, and has excellent dust resistance can be obtained. The thickness change rate of the resin foam caused by repeated compression is more preferably 8% or less, further preferably 5% or less, particularly preferably 3% or less, and most preferably 1% or less. If it is within this range, the above effect becomes significant. The smaller the thickness change rate of the resin foam caused by repeated compression, the better, but its lower limit is, for example, 0.5% (preferably 0.3%, more preferably 0.1%, and further preferably 0.05%). The thickness change rate of the resin foam caused by repeated compression refers to: a disc clamp with a flat front end (contact area: 4.9 cm 2 ) is pressed against the resin foam and subjected to 5000 cycles of 50% compression / 10% compression (thickness reference). The change rate is calculated by the formula (thickness before test) - (thickness after test) / (thickness before test) × 100.

[0065] The tensile modulus of the resin foam at 23°C is preferably 0.6 MPa or more, more preferably 0.7 MPa to 5 MPa, and further preferably 1 MPa to 4 MPa. If it is within such a range, a resin foam having excellent stress dispersion and excellent impact absorption can be obtained even in a thin film. The sample (size: 10 mm × 80 mm) is fixed at a distance of 40 mm between chucks, and a tensile strain-tensile strength curve is obtained by performing a tensile test at a tensile speed of 500 mm / min. The tensile modulus is obtained from the slope of a straight line connecting the origin of the curve and the tensile strength at a tensile strain of 10%.

[0066] The elongation at break of the above-mentioned resin foam at 25°C is preferably 120% or less, more preferably 110% or less, further preferably 100% or less, and particularly preferably 90% or less. If it is within such a range, a resin foam with excellent flexibility and stress dispersion can be obtained. It should be noted that if the elongation at break is small, when a load is applied to the resin foam, the deformation of the pore wall of the resin foam becomes smaller. For example, when a filler is added, sliding is likely to occur at the interface between the resin constituting the resin foam and the filler, which can further alleviate the load. On the other hand, if the elongation at break is too large, the deformation of the pore wall of the resin foam becomes larger, and there is a concern that it becomes difficult to alleviate the load. The elongation at break can be measured based on JIS K 6767.

[0067] The tensile stress retention rate of the above-mentioned resin foam is preferably 60% or more, more preferably 63% to 100%, and further preferably 63% to 95%. If it is within such a range, a resin foam with excellent stress dispersion and excellent impact absorption can be obtained even as a film. In this specification, the above-mentioned tensile stress retention rate refers to the ratio of the tensile strength just after stretching and the tensile strength after being maintained for 12 hours after stretching when the resin foam (width 10mm×length 100mm) is stretched 20% along the length direction at a speed of 300m / min (tensile strength after 12 hours / tensile strength just after stretching×100).

[0068] The thickness of the resin foam is preferably 30 μm to 5000 μm, more preferably 35 μm to 4000 μm, further preferably 40 μm to 3000 μm, further preferably 45 μm to 2000 μm, particularly preferably 50 μm to 1000 μm, and most preferably 55 μm to 500 μm. As described above, the resin foam of the present invention exhibits excellent impact resistance despite being a thin layer. In addition, if the thickness of the resin foam is within the above range, a fine and uniform bubble structure can be formed, which is advantageous in that excellent impact absorption can be exhibited.

[0069] The average bubble diameter (average pore diameter) of the above-mentioned resin foam is preferably 10μm to 200μm, more preferably 15μm to 180μm, further preferably 20μm to 150μm, further preferably 23μm to 120μm, particularly preferably 25μm to 100μm, and most preferably 30μm to 80μm. If it is within such a range, a resin foam that will not deform excessively when impacted and can exhibit high impact absorption can be obtained. In addition, a resin foam having moderate hardness and suitable as a cushioning material for filling gaps can be made. The method for measuring the average bubble diameter is described later.

[0070] The aspect ratio of the bubbles of the resin foam is preferably 1.5 or more. If it is within this range, a resin foam with excellent thickness recovery can be obtained. The aspect ratio of the bubbles constituting the resin foam is preferably 2.0 or more, more preferably 2.5 or more. If it is within this range, the above effect becomes significant. In addition, the upper limit of the aspect ratio of the bubbles constituting the resin foam is preferably 5, more preferably 4, and further preferably 3.5. If it is within this range, a resin foam with excellent impact absorption can be obtained.

[0071] It should be noted that, in this specification, the "aspect ratio of cells in a resin foam" refers to the aspect ratio of a cell in a given area (3 mm2) in a cross section of a resin foam at a randomly selected location. 2 ) is the average value of the aspect ratio of each bubble existing in the range of . The specific method for calculating the "aspect ratio of bubbles in the resin foam" is as follows.

[0072] The resin foam was cut along TD (direction perpendicular to the flow direction) and in a direction perpendicular to the main surface of the resin foam (thickness direction) using a razor, and a given area (3 mm 2 ) range. The length of a bubble in the thickness direction and the length TD are measured.

[0073] • Perform the same measurement on all bubbles present within a given area.

[0074] The aspect ratio of the cells is calculated by the length in the TD / the length in the thickness direction. The same calculation is performed for all the cells, and the average value is defined as the “aspect ratio of the cells in the resin foam”.

[0075] The coefficient of variation of the bubble diameter (pore diameter) of the resin foam of the present invention is preferably 0.5 or less, more preferably 0.48 or less, further preferably 0.45 or less, particularly preferably 0.43 or less, and most preferably less than 0.4. If it is within such a range, the deformation caused by the impact becomes uniform, local stress loads can be prevented, and a resin foam having excellent stress dispersion and particularly excellent impact resistance can be obtained. The smaller the coefficient of variation, the more preferred it is, and its lower limit is, for example, 0.2 (preferably 0.15, more preferably 0.1, and further preferably 0.01). The method for determining the coefficient of variation of the bubble diameter is described later.

[0076] The bubble rate (porosity) of the resin foam of the present invention is preferably 30% or more, more preferably 50% or more. If it is within such a range, a resin foam with a small repulsive stress during compression can be obtained. For such a resin foam, when the resin foam is slightly compressed at a position with a narrow gap and applied, the stress applied to other components can be reduced. For example, in the case where the resin foam is used for a display component, the stress applied to the display component can be relaxed / dispersed, so it is useful from the perspective of reducing color unevenness and protecting components. The upper limit of the bubble rate is preferably 99% or less, more preferably 95% or less, and further preferably 90% or less. If it is within such a range, a resin foam with moderate hardness, small deformation when impacted, and thus high impact absorption can be made. The method for measuring the bubble rate is described later.

[0077] The thickness of the cell wall (pore wall) of the resin foam of the present invention is preferably 0.1 μm to 10 μm, more preferably 0.3 μm to 8 μm, further preferably 0.5 μm to 5 μm, particularly preferably 0.7 μm to 4 μm, and most preferably 1 μm to 3 μm. If it is within such a range, a resin foam that will not deform excessively when impacted and can exhibit high impact absorption can be obtained. In addition, a resin foam having a moderate hardness and suitable as a cushioning material for filling gaps can be made. The method for measuring the thickness of the cell wall is described later.

[0078] In the case where the bubble structure of the resin foam of the present invention is a semi-continuous semi-independent bubble structure, the proportion of the independent bubble structure therein is preferably less than 40%, more preferably less than 30%. If it is within such a range, a resin foam having a moderate hardness and suitable as a cushioning material for filling gaps can be made. In this specification, the independent bubble rate of the resin foam is calculated, for example, as follows: in an environment with a temperature of 23°C and a humidity of 50%, the object to be measured is immersed in water, the mass after measurement is measured, and then the mass is measured again after being fully dried in an oven at 80°C. In addition, if it is a continuous bubble, it can retain moisture, so it can be measured as a continuous bubble and its mass can be obtained.

[0079] The resin foam of the present invention may adopt any appropriate shape depending on the purpose. A typical example of such a shape is a sheet.

[0080] The resin foam of the present invention may have a heat-melting layer on one or both sides. The resin foam having a heat-melting layer can be obtained, for example, by rolling the resin foam (or a precursor of the resin foam) using a pair of heating rollers heated to a temperature above the melting temperature of the resin composition constituting the resin foam.

[0081] The resin foam of the present invention can be formed by any appropriate method within the range not impairing the effects of the present invention. As such a method, a method of foaming a resin composition containing a resin material (polymer) is typically mentioned.

[0082] A-1. Resin composition

[0083] The resin foam of the present invention can be typically obtained by foaming a resin composition. The resin composition contains any appropriate resin material (polymer).

[0084] Examples of the polymer include acrylic resins, silicone resins, urethane resins, polyolefin resins, ester resins, rubber resins, etc. The polymers may be used alone or in combination of two or more.

[0085] The content of the polymer is preferably 30 to 95 parts by weight, more preferably 35 to 90 parts by weight, further preferably 40 to 80 parts by weight, and particularly preferably 40 to 60 parts by weight relative to 100 parts by weight of the resin composition. If it is within this range, a resin foam having better flexibility and stress dispersion can be obtained.

[0086] In one embodiment, a polyolefin resin is used as the polymer.

[0087] The content of the polyolefin resin is preferably 50 to 100 parts by weight, more preferably 70 to 100 parts by weight, further preferably 90 to 100 parts by weight, particularly preferably 95 to 100 parts by weight, and most preferably 100 parts by weight, relative to 100 parts by weight of the above-mentioned polymer.

[0088] As the polyolefin resin, at least one selected from polyolefin and polyolefin elastomer can be preferably cited, and it is more preferable to use a polyolefin and a polyolefin elastomer in combination. Polyolefin and polyolefin elastomer can be used alone or in combination of two or more. It should be noted that in this specification, when "polyolefin" is referred to, "polyolefin elastomer" is not included.

[0089] When polyolefin and polyolefin elastomer are used in combination as the polyolefin resin, the weight ratio of polyolefin to polyolefin elastomer (polyolefin / polyolefin elastomer) is preferably 1 / 99 to 99 / 1, more preferably 10 / 90 to 90 / 10, further preferably 20 / 80 to 80 / 20, and particularly preferably 30 / 70 to 70 / 30. Within such a range, the effect of the present invention becomes significant.

[0090] As the polyolefin, any appropriate polyolefin can be used within the range that does not impair the effect of the present invention. As such a polyolefin, for example, linear polyolefins, branched (branched) polyolefins, etc. can be cited. In one embodiment, as a polyolefin resin, a branched polyolefin is used. In this embodiment, as a polyolefin, only branched polyolefins can be used, or branched polyolefins and linear polyolefins can be used in combination. By using branched polyolefins, a resin foam having a small average bubble diameter and excellent impact resistance can be obtained. Relative to 100 parts by weight of polyolefin, the content ratio of the branched polyolefin is preferably 30 parts by weight to 100 parts by weight, and more preferably 80 parts by weight to 120 parts by weight.

[0091] As the above-mentioned polyolefin, for example, a polymer containing a structural unit derived from an α-olefin can be cited. The polyolefin may be composed of structural units derived from an α-olefin alone, or may be composed of structural units derived from an α-olefin and structural units derived from monomers other than the α-olefin. When the polyolefin is a copolymer, any appropriate copolymerization method can be adopted as its copolymerization method. For example, random copolymers, block copolymers, etc. can be cited.

[0092] As the α-olefin that can constitute the polyolefin, for example, α-olefins having 2 to 8 carbon atoms (preferably 2 to 6, more preferably 2 to 4) (for example, ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, etc.) are preferred. The α-olefins may be one type or two or more types.

[0093] Examples of monomers other than α-olefin constituting polyolefin include ethylenically unsaturated monomers such as vinyl acetate, acrylic acid, acrylic acid esters, methacrylic acid, methacrylic acid esters, and vinyl alcohol. The monomers other than α-olefin may be one type or two or more types.

[0094] Specific examples of polyolefins include low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, polypropylene (propylene homopolymer), copolymers of ethylene and propylene, copolymers of ethylene and α-olefins other than ethylene, copolymers of propylene and α-olefins other than propylene, copolymers of ethylene, propylene and α-olefins other than ethylene and propylene, copolymers of propylene and ethylenically unsaturated monomers, and the like.

[0095] In one embodiment, as the polyolefin, a polypropylene-based polymer having a structural unit derived from propylene is used. Examples of the polypropylene-based polymer include polypropylene (propylene homopolymer), copolymers of ethylene and propylene, copolymers of propylene and α-olefins other than propylene, etc., preferably polypropylene (propylene homopolymer). The polypropylene-based polymer may be used alone or in combination of two or more.

[0096] From the viewpoint of being able to further demonstrate the effect of the present invention, the melt flow rate (MFR) of the polyolefin at a temperature of 230° C. is preferably 0.2 g / 10 min to 10 g / 10 min, more preferably 0.25 g / 10 min to 5 g / 10 min, further preferably 0.3 g / 10 min to 3 g / 10 min, and particularly preferably 0.35 g / 10 min to 1.5 g / 10 min. It should be noted that in this specification, the melt flow rate (MFR) refers to the MFR measured under the conditions of a temperature of 230° C. and a load of 2.16 kgf based on ISO1133 (JIS-K-7210).

[0097] In one embodiment, two or more different polyolefins having a melt flow rate (MFR) at a temperature of 230° C. within the above range are used in combination. In this case, a polyolefin having a melt flow rate (MFR) at a temperature of 230° C. of preferably 0.2 g / 10 min or more and less than 0.7 g / 10 min (more preferably 0.2 g / 10 min to 0.65 g / 10 min) and a polyolefin having a melt flow rate (MFR) at a temperature of 230° C. of preferably 0.7 g / 10 min to 10 g / 10 min (more preferably 0.7 g / 10 min to 5 g / 10 min, further preferably 0.7 g / 10 min to 3 g / 10 min, particularly preferably 0.7 g / 10 min to 1.5 g / 10 min, and most preferably 0.7 g / 10 min to 1.3 g / 10 min) can be used in combination. In this way, a resin foam having a small average cell diameter and excellent impact resistance can be obtained.

[0098] When two or more different polyolefins having a melt flow rate (MFR) at a temperature of 230° C. within the above-mentioned range are used in combination as the polyolefin, for example, a polyolefin having a melt flow rate (MFR) at a temperature of 230° C. of preferably 0.2 g / 10 min or more and less than 0.7 g / 10 min (more preferably 0.2 g / 10 min to 0.65 g / 10 min), and a polyolefin having a melt flow rate (MFR) at a temperature of 230° C. of preferably 0.7 g / 10 min to 10 g / 10 min (more preferably The weight ratio of the polyolefin selected (0.7 g / 10 min to 5 g / 10 min, further preferably 0.7 g / 10 min to 3 g / 10 min, particularly preferably 0.7 g / 10 min to 1.5 g / 10 min, most preferably 0.7 g / 10 min to 1.3 g / 10 min) is preferably 1 / 99 to 99 / 1, more preferably 10 / 90 to 90 / 10, further preferably 20 / 80 to 80 / 20, particularly preferably 30 / 70 to 70 / 30, and most preferably 40 / 60 to 60 / 40.

[0099] As the polyolefin, commercially available products can be used, for example: "E110G" (manufactured by Prime Polymer Co., Ltd.), "EA9" (manufactured by Japan Polypropylene Co., Ltd.), "EA9FT" (manufactured by Japan Polypropylene Co., Ltd.), "E-185G" (manufactured by Prime Polymer Co., Ltd.), "WB140HMS" (manufactured by Borealis), "WB135HMS" (manufactured by Borealis), etc.

[0100] As the polyolefin elastomer, any appropriate polyolefin elastomer can be used within the scope that does not impair the effect of the present invention. As such polyolefin elastomer, for example, non-crosslinked thermoplastic olefin elastomers (TPO) such as ethylene-propylene copolymer, ethylene-propylene-diene copolymer, ethylene-vinyl acetate copolymer, polybutene, polyisobutylene, chlorinated polyethylene, elastomers obtained by physically dispersing a polyolefin component and a rubber component, and elastomers having a structure in which a polyolefin component and a rubber component are microphase-separated can be cited; dynamically crosslinked thermoplastic olefin elastomers (TPV) obtained by dynamically heat treating a mixture containing a resin component A (olefin resin component A) forming a matrix and a rubber component B forming a domain in the presence of a crosslinking agent; and the like, the dynamically crosslinked thermoplastic olefin elastomer is a polymer having a multiphase system having a sea island structure in which crosslinked rubber particles are finely dispersed as domains (island phases) in the resin component A as a matrix (sea phase).

[0101] The polyolefin elastomer preferably contains a rubber component. Examples of such a rubber component include rubber components described in Japanese Patent Application Laid-Open No. 08-302111, Japanese Patent Application Laid-Open No. 2010-241934, Japanese Patent Application Laid-Open No. 2008-024882, Japanese Patent Application Laid-Open No. 2000-007858, Japanese Patent Application Laid-Open No. 2006-052277, Japanese Patent Application Laid-Open No. 2012-072306, Japanese Patent Application Laid-Open No. 2012-057068, Japanese Patent Application Laid-Open No. 2010-241897, Japanese Patent Application Laid-Open No. 2009-067969, and Japanese Re-List No. 03 / 002654.

[0102] Specific examples of the elastomer having a structure in which a polyolefin component and an olefin rubber component undergo microphase separation include an elastomer formed from a polypropylene resin (PP) and an ethylene-propylene rubber (EPM), an elastomer formed from a polypropylene resin (PP) and an ethylene-propylene-diene rubber (EPDM), etc. The weight ratio of the polyolefin component to the olefin rubber component (polyolefin component / olefin rubber) is preferably 90 / 10 to 10 / 90, and more preferably 80 / 20 to 20 / 80.

[0103] Generally speaking, dynamically crosslinked thermoplastic olefin elastomers (TPVs) have a higher elastic modulus and a smaller compression set than non-crosslinked thermoplastic olefin elastomers (TPOs), so they have good resilience and can exhibit excellent resilience when made into foams.

[0104] A dynamically cross-linked thermoplastic olefin elastomer (TPV) is a polymer having a sea-island structure in which cross-linked rubber particles are finely dispersed as domains (island phases) in the resin component A as a matrix (sea phase), obtained by dynamically heat treating a mixture comprising a resin component A forming a matrix (olefin resin component A) and a rubber component B forming a domain in the presence of a cross-linking agent as described above.

[0105] Examples of the dynamically crosslinked thermoplastic olefin elastomer (TPV) include those described in JP-A-2000-007858, JP-A-2006-052277, JP-A-2012-072306, JP-A-2012-057068, JP-A-2010-241897, JP-A-2009-067969, and JP-A-03 / 002654.

[0106] As the dynamically crosslinked thermoplastic olefin elastomer (TPV), commercially available products may be used, and examples thereof include: "Zeotherm" (manufactured by Zeon Co., Ltd.), "THERMORUN" (manufactured by Mitsubishi Chemical Corporation), and "Sarlink 3245D" (manufactured by Toyobo Co., Ltd.).

[0107] The melt flow rate (MFR) of the polyolefin elastomer at a temperature of 230°C is preferably 2 g / 10 min to 15 g / 10 min, more preferably 3 g / 10 min to 10 g / 10 min, further preferably 3.5 g / 10 min to 9 g / 10 min, particularly preferably 4 g / 10 min to 8 g / 10 min, and most preferably 4.5 g / 10 min to 7.5 g / 10 min.

[0108] The melt tension (190° C., at break) of the polyolefin elastomer is preferably less than 10 cN, more preferably 5 cN to 9.5 cN.

[0109] The JIS A hardness of the polyolefin elastomer is preferably 30° to 95°, more preferably 35° to 90°, further preferably 40° to 88°, particularly preferably 45° to 85°, and most preferably 50° to 83°. The JIS A hardness is measured in accordance with ISO 7619 (JIS K6253).

[0110] In one embodiment, the resin foam (i.e., resin composition) may further include a filling material. By containing a filling material, a resin foam that requires a large amount of energy to deform the bubble wall (pore wall) can be formed, and the resin foam exhibits excellent impact absorption. In addition, by containing a filling material, a fine and uniform bubble structure can be formed, which is also advantageous in that excellent impact absorption can be exhibited. The filling material can be used alone or in combination of two or more.

[0111] The content of the filler is preferably 10 to 150 parts by weight, more preferably 30 to 130 parts by weight, and even more preferably 50 to 100 parts by weight relative to 100 parts by weight of the polymer constituting the resin foam.

[0112] In one embodiment, the filler is an inorganic substance. Examples of materials constituting the filler as an inorganic substance include aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, calcium silicate, magnesium silicate, calcium oxide, magnesium oxide, aluminum oxide, aluminum nitride, aluminum borate whisker, silicon nitride, boron nitride, crystalline silicon dioxide, amorphous silicon dioxide, metals (e.g., gold, silver, copper, aluminum, nickel), carbon, graphite, etc.

[0113] In one embodiment, the filler is an organic material. Examples of the material constituting the filler as an organic material include polymethyl methacrylate (PMMA), polyimide, polyamide-imide, polyetheretherketone, polyetherimide, and polyesterimide.

[0114] As the filler, a flame retardant may be used. Examples of the flame retardant include bromine flame retardants, chlorine flame retardants, phosphorus flame retardants, antimony flame retardants, etc. From the viewpoint of safety, it is preferred to use a halogen-free and antimony-free flame retardant.

[0115] Examples of halogen-free and antimony-free flame retardants include compounds containing aluminum, magnesium, calcium, nickel, cobalt, tin, zinc, copper, iron, titanium, boron, etc. Examples of such compounds (inorganic compounds) include hydrated metal compounds such as aluminum hydroxide, magnesium hydroxide, magnesium oxide / nickel oxide hydrates, and magnesium oxide / zinc oxide hydrates.

[0116] The filler may be subjected to any appropriate surface treatment, and examples of such surface treatment include silane coupling treatment and stearic acid treatment.

[0117] The bulk density of the filler is preferably 0.8 g / cm 3 Below, more preferably 0.6 g / cm 3 Below, more preferably 0.4 g / cm 3 Below, particularly preferably 0.3 g / cm 3 If the filler content is within this range, the filler can be contained with good dispersibility, and even if the filler content is reduced, the filler addition effect can be fully exerted. The resin foam with a small filler content is advantageous in terms of high foaming, softness, stress dispersion and excellent appearance. The lower limit of the bulk density of the filler is, for example, 0.01 g / cm 3 , preferably 0.05g / cm 3 , more preferably 0.1 g / cm 3 .

[0118] The number average particle size (primary particle size) of the above-mentioned filler is preferably less than 5 μm, more preferably less than 3 μm, and further preferably less than 1 μm. If it is such a range, the filler can be contained with good dispersibility, and a uniform bubble structure can be formed. As a result, a resin foam with excellent stress dispersion and appearance can be obtained. The lower limit of the number average particle size of the filler is, for example, 0.1 μm. The number average particle size of the filler can be measured by mixing a suspension prepared by mixing 1 g of filler in 100 g of water as a sample and using a particle size distribution meter (MicrtracII, MICROTRAC BEL Co., Ltd.).

[0119] The specific surface area of ​​the above-mentioned filling material is preferably 2m 2 / g or more, more preferably 4m 2 / g or more, more preferably 6m 2 / g or more. If it is within this range, the filler can be contained with good dispersibility and a uniform bubble structure can be formed. As a result, a resin foam with excellent stress dispersion and appearance can be obtained. The upper limit of the specific surface area of ​​the filler is, for example, 20m 2 The specific surface area of ​​the filler can be measured by the BET method, that is, by allowing molecules with a known adsorption area to be adsorbed on the surface of the filler at a low temperature using liquid nitrogen and measuring the specific surface area based on the adsorbed amount.

[0120] Any suitable other components can be included in the resin combination within the scope of not damaging the effect of the present invention. Such other components can be only one or more than two. As such other components, for example: rubber, resins other than the polymers coordinated as resin materials, softeners, aliphatic compounds, anti-aging agents, antioxidants, light stabilizers, weathering agents, ultraviolet light absorbers, dispersants, plasticizers, carbon, antistatic agents, surfactants, crosslinking agents, thickeners, rust inhibitors, organosilicon compounds, tension modifiers, shrinkage inhibitors, fluidity modifiers, gelling agents, curing agents, reinforcing agents, foaming agents, foaming nucleating agents, colorants (pigment, dyes, etc.), pH adjusting agents, solvents (organic solvents), thermal polymerization initiators, photopolymerization initiators, lubricants, crystallization nucleating agents, crystallization accelerators, vulcanizing agents, surface treatment agents, dispersing aids, etc. can be cited.

[0121] A-2. Formation of resin foam

[0122] The resin foam of the present invention is typically obtained by foaming a resin composition. As a foaming method (a method for forming bubbles), a method commonly used in foaming molding such as a physical method and a chemical method can be adopted. That is, the resin foam of the present invention can be typically a foam formed by foaming by a physical method (physical foam), or a foam formed by foaming by a chemical method (chemical foam). The physical method is generally a method (mechanical foam) in which gas components such as air and nitrogen are dispersed in a polymer solution and bubbles are formed by mechanical mixing. The chemical method is generally a method in which pores are formed by utilizing the gas generated by the thermal decomposition of a foaming agent added to a polymer matrix to obtain a foam.

[0123] The resin composition to be foamed can be prepared by mixing the constituent components using any appropriate melt-kneading device, such as an open mixing roll, a non-open Banbury mixer, a single-screw extruder, a twin-screw extruder, a continuous kneader, a pressure kneader, or any other appropriate mechanism.

[0124] <Embodiment 1 for forming the resin foam of the present invention>

[0125] As an embodiment 1 of forming the resin foam of the present invention, for example, the following methods can be cited: the resin foam is formed by a process (process A) of mechanically foaming an emulsion resin composition (emulsion containing a resin material (polymer) etc.). As a foaming device, for example: a high-speed shearing device, a vibration device, a pressurized gas ejection device, etc. can be cited. Among these foaming devices, from the viewpoint of miniaturization of bubble diameter and large-capacity production, a high-speed shearing device is preferred. This embodiment 1 of forming the resin foam of the present invention can be applied regardless of when it is formed by which resin composition.

[0126] From the viewpoint of film-forming properties, the higher the solid content concentration of the emulsion, the better. The solid content concentration of the emulsion is preferably 30% by weight or more, more preferably 40% by weight or more, and even more preferably 50% by weight or more.

[0127] The bubbles generated by mechanical stirring are formed by gas entering the emulsion. As the gas, any appropriate gas can be used as long as it is inactive to the emulsion without damaging the effect of the present invention. Examples of such gas include air, nitrogen, carbon dioxide, etc.

[0128] The resin foam of the present invention can be obtained by applying the foamed emulsion resin composition (bubble-containing emulsion resin composition) on a substrate and drying the emulsion resin composition (step B). Examples of the substrate include a release-treated plastic film (a release-treated polyethylene terephthalate film, etc.), a plastic film (a polyethylene terephthalate film, etc.), and the like.

[0129] In step B, any appropriate method may be adopted as the coating method and the drying method within the range that does not impair the effect of the present invention. Step B preferably includes: a preliminary drying step B1 of drying the bubble-containing emulsion resin composition coated on the substrate at a temperature of 50°C or higher and less than 125°C; and a main drying step B2 of further drying at a temperature of 125°C or higher and 200°C or lower.

[0130] By setting up a pre-drying process B1 and a formal drying process B2, it is possible to prevent the bubbles from being integrated and bursting due to a sharp temperature rise. In particular, for a foam sheet with a small thickness, the bubbles will be integrated and burst due to a sharp rise in temperature. Therefore, it is of great significance to set up a pre-drying process B1. The temperature in the pre-drying process B1 is preferably 50°C to 100°C. The time of the pre-drying process B1 is preferably 0.5 minutes to 30 minutes, and more preferably 1 minute to 15 minutes. The temperature in the formal drying process B2 is preferably 130°C to 180°C, and more preferably 130°C to 160°C. The time of the formal drying process B2 is preferably 0.5 minutes to 30 minutes, and more preferably 1 minute to 15 minutes.

[0131] <Embodiment 2 for forming the resin foam of the present invention>

[0132] As an embodiment 2 of forming the resin foam of the present invention, a method of forming a foam by foaming a resin composition with a foaming agent can be cited. As the foaming agent, a foaming agent commonly used in foam molding can be used, and from the perspective of environmental protection and low pollution to the foamed body, a high-pressure inert gas is preferably used.

[0133] As an inert gas, any appropriate inert gas can be used as long as it is inactive and can be impregnated with the resin composition. As such an inert gas, for example, carbon dioxide, nitrogen, air, etc. can be cited. These gases can also be used in combination. Among these, carbon dioxide is preferred from the viewpoint that the impregnation amount for the resin material (polymer) is large and the impregnation speed is fast.

[0134] The inert gas is preferably in a supercritical state. That is, it is particularly preferred to use carbon dioxide in a supercritical state. In a supercritical state, the solubility of the inert gas in the resin composition is further increased, and the inert gas can be mixed in a high concentration, and when the pressure drops sharply, the inert gas becomes a high concentration, so the generation of bubble nuclei becomes more, and even if the porosity is the same, the density of the bubbles that can be formed by the growth of the bubble nuclei is also greater than that in other states, so fine bubbles can be obtained. It should be noted that the critical temperature of carbon dioxide is 31°C and the critical pressure is 7.4MPa.

[0135] As a method for forming a foamed body by impregnating a resin composition with a high-pressure inert gas, for example, a method formed by the following steps can be cited: a gas impregnation step of impregnating an inert gas in a resin composition containing a resin material (polymer) under high pressure; a decompression step of reducing the pressure after the step to foam the resin material (polymer); and a heating step of growing bubbles by heating as required. In this case, the pre-formed unfoamed molded body can be immersed in an inert gas, and the inert gas can also be impregnated in a molten resin composition under a pressurized state and then molded under reduced pressure. These steps can be performed in any of an intermittent manner and a continuous manner. That is, it can be an intermittent manner in which the resin composition is pre-formed into a suitable shape such as a sheet and made into an unfoamed resin molded body, and then the unfoamed resin molded body is impregnated with a high-pressure gas and the pressure is released to foam; it can also be a continuous manner in which the resin composition is kneaded and molded together with a high-pressure gas under pressure, and the pressure is released to simultaneously mold and foam.

[0136] The following shows an example of making a foamed body in an intermittent manner. For example, a resin sheet for foam molding is made by extruding a resin composition using an extruder such as a single screw extruder or a twin screw extruder. Alternatively, a mixing machine provided with blades such as a roller, a cam, a kneading machine, a Banbury type, etc. is used to uniformly mix the resin composition in advance, and then the unfoamed resin molded body is processed into a given thickness by pressing with a hot plate, etc. The unfoamed resin molded body obtained in this way is placed in a high-pressure container, injected with a high-pressure inert gas (carbon dioxide in a supercritical state, etc.), and infiltrated with an inert gas in the unfoamed resin molded body. At the moment when the inert gas is fully infiltrated, the pressure is released (usually to atmospheric pressure) to generate bubble nuclei in the resin. The bubble nuclei can be grown directly at room temperature, but according to the circumstances, they can also be grown by heating. As a method of heating, known and commonly used methods such as a water bath, an oil bath, a hot roller, a hot air oven, far infrared rays, near infrared rays, and microwaves can be used. After the bubbles are grown in this way, they are rapidly cooled by cold water or the like to fix the shape, thereby obtaining a foamed body. It should be noted that the unfoamed resin molded body for foaming is not limited to a sheet-like object, and unfoamed resin molded bodies of various shapes can also be used according to the purpose. In addition, the unfoamed resin molded body for foaming can also be produced by other molding methods such as injection molding in addition to extrusion molding and pressure molding.

[0137] The example of making a foamed body in a continuous manner is shown below. For example, foam molding is carried out by the following mixing and impregnation process and molding decompression process, in which a resin composition is mixed by an extruder such as a single screw extruder and a twin screw extruder while injecting (importing) a high-pressure gas (particularly an inactive gas, and then carbon dioxide) so that the high-pressure gas is fully impregnated in the resin composition; the molding decompression process extrude the resin composition by a die head arranged at the front end of the extruder, thereby releasing the pressure (usually to atmospheric pressure), and molding and foaming are carried out simultaneously. In addition, when foam molding is carried out in a continuous manner, a heating process for growing bubbles by heating can be provided as needed. After the bubbles are grown in this way, the shape can be fixed by cooling rapidly by cold water, etc. as needed. In addition, the introduction of high-pressure gas can be carried out continuously or discontinuously. In addition, in the mixing and impregnation process and the molding decompression process, for example, an extruder or an injection molding machine can be used. It should be noted that any appropriate method such as a water bath, an oil bath, a hot roller, a hot air oven, far infrared rays, near infrared rays, and microwaves can be cited as a heating method for growing the bubble nuclei. Any appropriate shape can be adopted as the shape of the foam. Examples of such shapes include sheet-like, prism-like, cylindrical, and special-shaped shapes.

[0138] From the perspective of obtaining a highly foamed foam, the amount of gas mixed when the resin composition is foam-molded is, for example, preferably 2 to 10 wt %, more preferably 2.5 to 8 wt %, and even more preferably 3 to 6 wt % relative to the total amount of the resin composition.

[0139] The pressure when the inert gas is impregnated in the resin composition can be appropriately selected considering operability, etc. Such a pressure is, for example, preferably more than 6MPa (for example, 6MPa to 100MPa), more preferably more than 8MPa (for example, 8MPa to 50MPa). It should be noted that, from the viewpoint of maintaining the supercritical state of carbon dioxide, the pressure in the case of using carbon dioxide in a supercritical state is preferably more than 7.4MPa. When the pressure is lower than 6MPa, the bubble growth during foaming is significant, the bubble diameter becomes too large, and sometimes the preferred average pore diameter (average bubble diameter) cannot be obtained. This is because, when the pressure is low, the impregnation amount of the gas is relatively less than that during high pressure, the bubble nucleus formation speed is reduced, and the number of bubble nuclei formed decreases, so the average gas amount per bubble increases instead, and the bubble diameter becomes extremely large. In addition, in the pressure region lower than 6MPa, only a slight change in the impregnation pressure will cause the bubble diameter and bubble density to change significantly, so the control of the bubble diameter and bubble density tends to become difficult.

[0140] The temperature in the gas impregnation process varies depending on the inert gas used, the type of components in the resin composition, etc., and can be selected within a wide range. Taking into account operability, etc., it is preferably 10°C to 350°C. The impregnation temperature when the unfoamed molded body is impregnated with an inert gas is preferably 10°C to 250°C, and more preferably 40°C to 230°C in the case of an intermittent method. In addition, the impregnation temperature when the molten polymer impregnated with gas is extruded and foamed and molded simultaneously is preferably 60°C to 350°C in the case of a continuous method. It should be noted that when carbon dioxide is used as an inert gas, in order to maintain a supercritical state, the temperature during impregnation is preferably above 32°C, and more preferably above 40°C.

[0141] In the decompression step, the decompression rate is preferably 5 MPa / sec to 300 MPa / sec in order to obtain uniform fine bubbles.

[0142] The heating temperature in the heating step is preferably 40°C to 250°C, more preferably 60°C to 250°C.

[0143] B. Foam components

[0144] Figure 1 1 is a schematic cross-sectional view of a foam member according to one embodiment of the present invention. The foam member 100 includes a resin foam layer 10 and an adhesive layer 20 disposed on at least one side of the resin foam layer 10. The resin foam layer 10 is composed of the above-mentioned resin foam.

[0145] The thickness of the adhesive layer is preferably 5 to 300 μm, more preferably 6 to 200 μm, further preferably 7 to 100 μm, and particularly preferably 8 to 50 μm. When the thickness of the adhesive layer is within the above range, the foam material of the present invention can exhibit excellent impact absorption properties.

[0146] As the adhesive layer, a layer formed by any appropriate adhesive can be used. As the adhesive constituting the adhesive layer, for example, rubber adhesives (synthetic rubber adhesives, natural rubber adhesives, etc.), urethane adhesives, acrylic urethane adhesives, acrylic adhesives, silicone adhesives, polyester adhesives, polyamide adhesives, epoxy adhesives, vinyl alkyl ether adhesives, fluorine adhesives, rubber adhesives, etc. can be listed. As the adhesive constituting the adhesive layer, it is preferably selected from at least one of acrylic adhesives, silicone adhesives, and rubber adhesives. Such adhesives can be only one type or more than two types. The adhesive layer can be one layer or more than two layers.

[0147] As adhesives, if classified by the bonding method, for example, there are emulsion adhesives, solvent adhesives, ultraviolet crosslinking type (UV crosslinking type) adhesives, electron beam crosslinking type (EB crosslinking type) adhesives, hot melt adhesives (hot melt adhesives), etc. Such adhesives may be only one type or two or more types.

[0148] The water vapor permeability of the adhesive layer is preferably 50 (g / (m 2 · 24 hours)) or less, more preferably 30 (g / (m 2 · 24 hours)) or less, more preferably 20 (g / (m 2 · 24 hours)) or less, particularly preferably 10 (g / (m 2 · 24 hours)). If the water vapor permeability of the adhesive layer is within the above range, the foam sheet of the present invention can stabilize the impact absorption without being affected by moisture. It should be noted that the water vapor permeability can be measured, for example, by a method based on JIS Z0208 under test conditions of 40°C and a relative humidity of 92%.

[0149] Any appropriate other components can be included in the adhesive constituting the adhesive layer within the scope of not damaging the effect of the present invention. As other components, for example: other polymer components, softeners, anti-aging agents, curing agents, plasticizers, filling materials, antioxidants, thermal polymerization initiators, photopolymerization initiators, ultraviolet absorbers, light stabilizers, colorants (pigments, dyes, etc.), solvents (organic solvents), surfactants (for example, ionic surfactants, silicone surfactants, fluorine surfactants, etc.), crosslinking agents (for example, polyisocyanate crosslinking agents, silicone crosslinking agents, epoxy crosslinking agents, alkyl etherified melamine crosslinking agents, etc.), etc. It should be noted that thermal polymerization initiators and photopolymerization initiators can be included in the materials used to form polymer components.

[0150] The foamed component of the present invention can be manufactured by any appropriate method. For example, the manufacturing method of the foamed component of the present invention includes: a method of manufacturing by laminating a resin foam layer and an adhesive layer; a method of manufacturing by forming an adhesive layer by a curing reaction after laminating a material forming the adhesive layer and the resin foam layer.

[0151] Example

[0152] Hereinafter, the present invention will be specifically described by examples, but the present invention is not limited to these examples. It should be noted that the test and evaluation methods in the examples are as follows. It should be noted that when it is recorded as "parts", it means "parts by weight" unless otherwise specified, and when it is recorded as "%", it means "% by weight" unless otherwise specified.

[0153] [Evaluation method]

[0154] <50% compression load>

[0155] The compression hardness of the foam was measured according to the method for measuring the compression hardness of the foam described in JIS K 6767. Specifically, the resin foam obtained in the examples / comparative examples was cut into 30 mm × 30 mm pieces as test pieces, and compressed at a compression rate of 10 mm / min until the compression rate reached 50%. The stress (N) at this time was converted into the average per unit area (1 cm 2 ) value, as the 25% compression load (N / cm 2 )、50% compression load (N / cm 2 ).

[0156] <Compression stress retention rate (after 6 hours and 12 hours)>

[0157] Using a precision universal testing machine (Autograph AG-X plus, manufactured by Shimadzu Corporation), the resin foam obtained in the embodiment / comparative example was cut into 30 mm × 30 mm size as a test piece, and the stress just after compression at a compression rate of 10 mm / min to a compression rate of 50% was set as (N1), and the stress after maintaining displacement after reaching a compression rate of 50% and a given time (6 hours, 12 hours) was set as (N2). Then, the compression stress retention rate [%] = N2 / N1 × 100 was calculated.

[0158] <Apparent density>

[0159] The density (apparent density) of the resin foam was calculated as follows: The resin foam obtained in the Examples / Comparative Examples was punched into a 20 mm x 20 mm test piece, the size of the test piece was measured with a caliper, and then the weight of the test piece was measured with an electronic balance and calculated using the following formula.

[0160] Apparent density (g / cm 3 ) = weight of test piece / volume of test piece

[0161] <Average cell diameter (average pore diameter) and coefficient of variation of cell diameter (pore diameter)>

[0162] The resin foam was cut along TD (direction perpendicular to the flow direction) and in the direction perpendicular to the main surface of the resin foam (thickness direction) using a razor, and a digital microscope (trade name "VHX-500", manufactured by Keyence Co., Ltd.) was used as a measuring instrument to import an enlarged image of the bubble portion of the resin foam, and the image analysis software of the same measuring instrument was used to obtain the number average bubble diameter (average pore diameter) (μm) by performing image analysis. It should be noted that the number of bubbles in the imported enlarged image is about 400. In addition, the standard deviation is calculated based on all the data of the pore diameter, and the coefficient of variation is calculated using the following formula.

[0163] Coefficient of variation = standard deviation / average bubble diameter (average pore diameter)

[0164] <Aspect ratio of bubbles>

[0165] The aspect ratio of cells in the resin foams obtained in Examples and Comparative Examples was measured by the following method using a digital microscope (trade name "VHX-2000, manufactured by Keyence Corporation) as a measuring instrument.

[0166] The resin foam is cut along TD (direction perpendicular to the flow direction) and in a direction perpendicular to the main surface of the resin foam (thickness direction) using a razor, and a predetermined area (3 mm2) of the cross section is observed at a magnification of 100 times using a microscope (e.g., Keyence "VHX-2000"). 2 ) range, measure the length of a bubble in the thickness direction and the length TD.

[0167] • Perform the same measurement on all bubbles present in a given area.

[0168] The aspect ratio of the cells is calculated by the length in the TD / the length in the thickness direction. The same calculation is performed for all the cells, and the average value is defined as the “aspect ratio of the cells in the resin foam”.

[0169] <Bubble ratio (porosity)>

[0170] The measurement was performed in an environment of a temperature of 23°C and a humidity of 50%. The resin foam obtained in the example / comparative example was punched out by a 100mm×100mm punching die (2-piece processing knife (trade name "NCA07", thickness 0.5mm, blade tip angle 45°, manufactured by NAKAYAMA Co., Ltd.)), and the size of the punched sample was measured. In addition, the thickness was measured using a 1 / 100 micrometer with a measuring terminal diameter (φ) of 20mm. Based on these values, the volume of the resin foam obtained in the example / comparative example was calculated. Next, the weight of the resin foam obtained in the example / comparative example was measured using a pan balance with a minimum scale of 0.01g or more. Based on these values, the bubble rate (porosity) of the resin foam obtained in the example / comparative example was calculated.

[0171] <Thickness of cell wall (pore wall)>

[0172] The resin foam was cut along TD (direction perpendicular to the flow direction) and in a direction perpendicular to the main surface of the resin foam (thickness direction) using a razor, and a digital microscope (trade name "VHX-500", manufactured by Keyence Co., Ltd.) was used as a measuring instrument to import an enlarged image of the bubble portion of the resin foam, and the thickness (μm) of the bubble wall (pore wall) was obtained by image analysis using the analysis software of the same measuring instrument. It should be noted that the number of bubbles in the imported enlarged image was about 400.

[0173] <Non-foaming bending stress>

[0174] The resin foam was pressurized at a temperature of (melting point + 70° C.) and a pressure of 15 MPa for 5 minutes using a vacuum press molding machine (IVM-70: Iwaki Industry Co., Ltd.), thereby obtaining a resin molded body a in a non-foamed state.

[0175] The resin molded body a was cut into a piece with a width of 6 mm and a length of 50 mm as a sample, and the sample was placed on a 3-point bending fixture with a support point distance of 25 mm. An indentation test was performed at an indentation speed of 0.5 mm / min in an environment of 23°C × 50% RH (manufactured by Shimadzu Corporation, trade name "AG-Xplus"). The load (g) when the sample was pressed 5 mm was taken as the non-foaming bending stress.

[0176] <Compression modulus>

[0177] Based on the compression test of JIS K 6767, the compression rate (%) and compression rebound force (kPa) of the resin foam are measured, and the compression rebound force F(5%) at a compression rate of 5% and the compression rebound force F(15%) at a compression rate of 15% are read respectively. The compression modulus is calculated based on F(5%) and F(15%) and the formula (F(15%)-F(5%)) / (15-5)×100.

[0178] <Thickness recovery rate>

[0179] For the resin foam, a 1000 g / cm 2 The resin foam is held under a load of 120 seconds, the compression is released, and the thickness of the resin foam 0.5 seconds after the compression is released (the thickness 0.5 seconds after the compression is released) is measured. The thickness recovery rate is calculated by the following formula based on the "thickness 0.5 seconds after the compression is released" and the thickness of the resin foam before the load is applied (initial thickness).

[0180] Thickness recovery rate (%) = {(thickness 0.5 seconds after release of compression) / (initial thickness)}×100

[0181] <Thickness change rate due to repeated compression>

[0182] Using a micro servo (MMT-250NV-10, manufactured by Shimadzu Corporation), a disk jig (Compression accessory disk type compression jig PC-5040, contact area: 4.9 cm) with a flat tip was used. 2 , IMADA Co., Ltd.) was repeatedly displaced relative to the foam body in a manner of 50% compression and 10% compression, and repeated compression was performed 5000 times (initial load 0.15N, descending speed 5min / mm, ascending speed 5min / mm). The thickness after the test was measured using a digital microscope (trade name "VHX-500", manufactured by Keyence Co., Ltd.). The thickness before the test was set to Z0, and the thickness after the test was set to Z1. The thickness change rate caused by repeated compression was calculated according to the formula (Z0-Z1) / Zo×100.

[0183] <Shock absorption rate>

[0184] A test body was formed by placing a resin foam, a double-sided tape (Model: No. 5603W, manufactured by Nitto Denko) and a PET film (Model: DIAFOIL MRF75, manufactured by Mitsubishi Plastics) on the impact force sensor in this order. A 66 g iron ball was dropped from a height of 50 cm above the PET film onto the test body, and the impact force F1 was measured.

[0185] In addition, the iron ball was directly dropped onto the impact force sensor as described above, and the blank impact force F0 was measured.

[0186] The impact absorption rate (%) was calculated from F1 and F0 using the formula (F0-F1) / F0×100.

[0187] <Stress dispersion>

[0188] Figure 2 1 is a schematic cross-sectional view showing a stress relaxation testing machine 1000 used for measuring the stress dispersion degree.

[0189] like Figure 2 As shown in FIG. 1 , a polycarbonate plate (200 mm×300 mm×1 mm thick) 200 is placed on an iron support A, and a stress measurement film 300 (trade name “Prescale” (two sheets, for micro-pressure (4LW), manufactured by Fujifilm Co., Ltd., sheets having a partially colored surface when pressed, 50 mm×50 mm×0.16 mm thick) is placed on the stress measurement film 300. Next, the resin foam structure obtained in the embodiment / comparative example to be measured is placed on the stress measurement film 300. (150mm×200mm×thickness 0.5mm) 400, on which a double-sided adhesive tape (No.5603, manufactured by Nitto Denko, thickness 0.03mm) 500 was pasted, a spacer 600 with a thickness of 0.05mm was configured, and an ABS plate (200mm×300mm×thickness 3mm) 700 was placed on the top. After 12 hours after assembly, a steel ball SUS304 (φ25mm) 800 was placed at the center from above, and a load of 20N was applied for 1 minute.

[0190] Then, the color change of the stress measurement film 300 is observed, and the color is not spread from the center of the stress measurement film 300 but becomes a dot, which is designated as C; the color is spread from the center of the stress measurement film 300 to 25 mm, which is designated as B; and the color is widely spread from the center of the stress measurement film 300 to the 50 mm end, which is designated as A.

[0191] [Example 1]

[0192] 65 parts by weight of polypropylene (melt flow rate (MFR) (230°C): 0.40 g / 10 min), 35 parts by weight of polyolefin elastomer (melt flow rate (MFR): 6 g / 10 min, JIS A hardness: 79°), 80 parts by weight of magnesium hydroxide (trade name "KISUMA 5P" manufactured by Kyowa Chemical Industry), 10 parts by weight of carbon (trade name "Asahi #35" manufactured by Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at 200°C using a twin-screw kneader manufactured by The Japan Steel Works, Ltd. (JSW), extruded in a strand form, and water-cooled to form pellets. The pellets were charged into a single-screw extruder manufactured by The Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 4.5 parts by weight to 100 parts by weight of the resin. After being fully saturated with carbon dioxide gas, the mixture was cooled to a temperature suitable for foaming and extruded from a die to obtain a sheet-like molded body. The sheet-like molded body was sliced ​​using a slicer to obtain a foamed structure a1 having a thickness of 0.3 mm.

[0193] Furthermore, the foamed structure a1 was passed between a pair of rolls (gap between rolls) of which one roll was heated to 200° C., to obtain a resin foam A having a thickness of 0.1 mm. The gap between the rolls was set so as to obtain a resin foam A having a thickness of 0.1 mm.

[0194] The obtained resin foam A was subjected to the above-mentioned evaluation. Table 1 shows the results.

[0195] [Example 2]

[0196] 65 parts by weight of polypropylene (melt flow rate (MFR) (230°C): 0.40 g / 10 min), 35 parts by weight of polyolefin elastomer (melt flow rate (MFR): 6 g / 10 min, JIS A hardness: 79°), 100 parts by weight of magnesium hydroxide (trade name "KISUMA 5P" manufactured by Kyowa Chemical Industry), 10 parts by weight of carbon (trade name "Asahi #35" manufactured by Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at 200°C using a twin-screw kneader manufactured by The Japan Steel Works, Ltd. (JSW), extruded in a strand form, and water-cooled to form pellets. The pellets were charged into a single-screw extruder manufactured by The Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere at 220°C. The carbon dioxide gas was injected at a ratio of 3.5 parts by weight to 100 parts by weight of the resin. After being fully saturated with carbon dioxide gas, the mixture was cooled to a temperature suitable for foaming and extruded from a die to obtain a sheet-like molded body. The sheet-like molded body was sliced ​​using a slicer to obtain a foamed structure b1 having a thickness of 0.3 mm.

[0197] Furthermore, the foamed structure b1 was passed between a pair of rolls (gap between rolls) of which one roll was heated to 200°C, to obtain a resin foam B having a thickness of 0.1 mm. The gap between the rolls was set so that a resin foam B having a thickness of 0.1 mm could be obtained.

[0198] The obtained resin foam B was subjected to the above-mentioned evaluation. Table 1 shows the results.

[0199] [Example 3]

[0200] 65 parts by weight of polypropylene (melt flow rate (MFR) (230°C): 0.40 g / 10 min), 35 parts by weight of polyolefin elastomer (melt flow rate (MFR): 6 g / 10 min, JIS A hardness: 79°), 120 parts by weight of magnesium hydroxide (trade name "KISUMA 5P" manufactured by Kyowa Chemical Industry), 10 parts by weight of carbon (trade name "Asahi #35" manufactured by Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at 200°C using a twin-screw kneader manufactured by The Japan Steel Works, Ltd. (JSW), extruded in a strand form, and water-cooled to form pellets. The pellets were charged into a single-screw extruder manufactured by The Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere at 220°C. The carbon dioxide gas was injected at a ratio of 3.0 parts by weight relative to 100 parts by weight of the resin. After being fully saturated with carbon dioxide gas, the mixture was cooled to a temperature suitable for foaming and extruded from a die to obtain a sheet-like molded body. The sheet-like molded body was sliced ​​using a slicer to obtain a foamed structure c1 having a thickness of 0.3 mm.

[0201] Furthermore, the resin foam c1 was passed between a pair of rolls (gap between rolls) of which one roll was heated to 200° C., to obtain a resin foam C having a thickness of 0.1 mm. The gap between the rolls was set so as to obtain a resin foam C having a thickness of 0.1 mm.

[0202] The obtained resin foam C was subjected to the above-mentioned evaluation. Table 1 shows the results.

[0203] [Example 4]

[0204] Using a twin-screw kneader manufactured by The Japan Steel Works, Ltd. (JSW), 15 parts by weight of polypropylene (melt flow rate (MFR) (230°C): 0.40 g / 10 min), 15 parts by weight of polypropylene (melt flow rate (MFR) (230°C): 1.1 g / 10 min), 75 parts by weight of a polyolefin elastomer (melt flow rate (MFR): 6 g / 10 min, JIS A hardness: 79°), 80 parts by weight of magnesium hydroxide (trade name "KISUMA 5P", manufactured by Kyowa Chemical Industry), 10 parts by weight of carbon (trade name "Asahi #35", manufactured by Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at 200°C, extruded in a strand form, and water-cooled to form pellets. The pellets were put into a single screw extruder manufactured by Nippon Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 2.8 parts by weight relative to 100 parts by weight of the resin. After the carbon dioxide gas was fully saturated, it was cooled to a temperature suitable for foaming and extruded from a die head to obtain a sheet-like molded body. The sheet-like molded body was thinned using a slicer to obtain a foamed structure d1 with a thickness of 0.4 mm.

[0205] Furthermore, the foamed structure d1 was passed between a pair of rolls (gap between rolls) of which one roll was heated to 200°C, to obtain a resin foam D having a thickness of 0.1 mm. The gap between the rolls was set so that a resin foam D having a thickness of 0.1 mm could be obtained.

[0206] The obtained resin foam D was subjected to the above-mentioned evaluation. Table 1 shows the results.

[0207] [Example 5]

[0208] Using a twin-screw kneader manufactured by The Japan Steel Works, Ltd. (JSW), 15 parts by weight of polypropylene (melt flow rate (MFR) (230°C): 0.40 g / 10 min), 15 parts by weight of polypropylene (melt flow rate (MFR) (230°C): 1.1 g / 10 min), 75 parts by weight of a polyolefin elastomer (melt flow rate (MFR): 6 g / 10 min, JIS A hardness: 79°), 60 parts by weight of magnesium hydroxide (trade name "KISUMA 5P", manufactured by Kyowa Chemical Industry), 10 parts by weight of carbon (trade name "Asahi #35", manufactured by Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at 200°C, extruded in a strand form, and water-cooled to form pellets. The pellets were put into a single screw extruder manufactured by Nippon Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 2.6 parts by weight relative to 100 parts by weight of the resin. After the carbon dioxide gas was fully saturated, it was cooled to a temperature suitable for foaming and extruded from a die to obtain a sheet-like molded body. The sheet-like molded body was thinned using a slicer to obtain a foamed structure e1 with a thickness of 0.4 mm.

[0209] Furthermore, the foamed structure e1 was passed between a pair of rolls (gap between rolls) of which one roll was heated to 200° C., to obtain a resin foam E having a thickness of 0.1 mm. The gap between the rolls was set so that a resin foam E having a thickness of 0.1 mm could be obtained.

[0210] The obtained resin foam E was subjected to the above-mentioned evaluation. Table 1 shows the results.

[0211] [Comparative Example 1]

[0212] 45 parts by weight of polypropylene (melt flow rate (MFR) (230°C): 0.40 g / 10 min), 55 parts by weight of polyolefin elastomer (melt flow rate (MFR): 6 g / 10 min, JIS A hardness: 79°), 10 parts by weight of magnesium hydroxide (trade name "KISUMA 5P" manufactured by Kyowa Chemical Industry), 10 parts by weight of carbon (trade name "Asahi #35" manufactured by Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at 200°C using a twin-screw kneader manufactured by The Japan Steel Works, Ltd. (JSW), extruded in a strand form, and water-cooled to form pellets. The pellets were charged into a single-screw extruder manufactured by The Japan Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere at 220°C. Carbon dioxide gas was injected at a ratio of 5.5 parts by weight relative to 100 parts by weight of the resin. After being fully saturated with carbon dioxide gas, the mixture was cooled to a temperature suitable for foaming and extruded from a die to obtain a sheet-like molded body. The sheet-like molded body was sliced ​​using a slicer to obtain a foamed structure f1 having a thickness of 0.3 mm.

[0213] Furthermore, the foamed structure f1 was passed between a pair of rolls (gap between rolls) of which one roll was heated to 200°C, to obtain a resin foam F having a thickness of 0.1 mm. The gap between the rolls was set so that a resin foam F having a thickness of 0.1 mm could be obtained.

[0214] The obtained resin foam F was subjected to the above-mentioned evaluation. Table 1 shows the results.

[0215] [Comparative Example 2]

[0216] Using a twin-screw kneader manufactured by The Japan Steel Works, Ltd. (JSW), 15 parts by weight of polypropylene (melt flow rate (MFR) (230°C): 0.40 g / 10 min), 15 parts by weight of polypropylene (melt flow rate (MFR) (230°C): 1.1 g / 10 min), 75 parts by weight of a polyolefin elastomer (melt flow rate (MFR): 6 g / 10 min, JIS A hardness: 79°), 80 parts by weight of magnesium hydroxide (trade name "KISUMA 5P", manufactured by Kyowa Chemical Industry), 10 parts by weight of carbon (trade name "Asahi #35", manufactured by Asahi Carbon Co., Ltd.), and 1 part by weight of stearic acid monoglyceride were kneaded at 200°C, extruded in a strand form, and water-cooled to form pellets. The pellets were put into a single screw extruder manufactured by Nippon Steel Works, Ltd., and carbon dioxide gas was injected at a pressure of 13 MPa (12 MPa after injection) in an atmosphere of 220°C. Carbon dioxide gas was injected at a ratio of 2.8 parts by weight relative to 100 parts by weight of the resin. After the carbon dioxide gas was fully saturated, it was cooled to a temperature suitable for foaming and extruded from a die head to obtain a sheet-like molded body. The sheet-like molded body was thinned using a slicer to obtain a resin foam G with a thickness of 0.1 mm.

[0217] The obtained resin foam G was subjected to the above-mentioned evaluation. The results are shown in Table 1.

[0218] [Table 1]

[0219] Example 1 Example 2 Example 3 Example 4 Example 5 Comparative Example 1 Comparative Example 2 <![CDATA[50% Compressive Load [N / cm 2 > 12 20 15 10 10 2 3.8 Compressive stress retention after 6 hours 85 84 83 85 84 44 82 Compressive stress retention after 12 hours 84 82 80 83 82 42 80 <![CDATA[Apparent density [g / cm 3 > 0.11 0.14 0.14 0.12 0.14 0.1 0.07 Bubble diameter [μm] 40 70 80 100 95 75 100 Bubble variation coefficient [-] 0.35 0.32 0.3 0.4 0.42 0.4 0.4 Bubble aspect ratio 1.6 1.9 2.8 3.2 3.1 1.8 1.2 Bubble rate [%] 90 88 85 88 86 90 93 Thickness of pore wall [μm] 2 2.5 2.2 2.6 2.6 1 1 Non-foamed bending stress [MPa] 13 13.5 10.2 9.4 6.5 3.5 40 Compression modulus [kPa] 265 300 370 220 205 22 500 Thickness recovery rate [%] 92 90 88 91 92 70 75 Thickness change rate due to repeated compression [%] 1.2 1.1 1 0.8 0.8 7.3 1.1 Shock absorption rate [%] 40 45 40 30 30 20 24 Stress dispersion A A A A A C B

[0220] As shown in Table 1, the resin foam of the present invention is excellent in "stress dispersion". Such a resin foam is advantageous in that it can prevent display unevenness due to pressure when applied to an image display device.

[0221] Industrial Applicability

[0222] The resin foam of the present invention can be suitably used as a cushioning material for electronic devices, for example.

Claims

1. A resin foam comprising a polyolefin resin, wherein the polyolefin resin is a mixture of a polyolefin other than a polyolefin elastomer and a polyolefin elastomer, The 50% compression load of the resin foam is 5 N / cm 2 ~30N / cm 2 The compressive stress retention rate after 6 hours is more than 60%, the compressive stress retention rate after 12 hours is more than 50%, and it has a bubble structure.

2. The resin foam according to claim 1, wherein the 50% compression load is 10 N / cm 2 ~30N / cm 2 . 3 . The resin foam according to claim 1 , which has a compression modulus of 200 kPa or more. 4 . The resin foam according to claim 1 , which has a non-foamed bending stress of 5 MPa or more. 5 . The resin foam according to claim 1 , wherein the thickness change rate due to repeated compression is 10% or less.

6. The resin foam according to claim 1 or 2, wherein the apparent density is 0.02 g / cm 3 ~0.50g / cm 3 .

7. The resin foam according to claim 1 or 2, which has a thickness recovery rate of 75% or more.

8. The resin foam according to claim 1 or 2, wherein The resin foam has cells having an aspect ratio of 1.5 or more. 9 . The resin foam according to claim 1 , wherein the average cell diameter is 10 μm to 200 μm.

10. The resin foam according to claim 1 or 2, which has a cell ratio of 30% or more. 11 . The resin foam according to claim 1 , wherein the coefficient of variation of cell diameter is 0.5 or less. 12 . The resin foam according to claim 1 , wherein the thickness of the cell wall is 0.1 μm to 10 μm.

13. The resin foam according to claim 1 or 2, wherein The resin foam has a heat-fusible layer on one or both sides.

14. A foam member comprising a resin foam layer and an adhesive layer disposed on at least one side of the resin foam layer, The resin foam layer is the resin foam according to any one of claims 1 to 13.

Citation Information

Patent Citations

  • Thermoplastic elastomer composition

    JP1996302111A

  • Thermoplastic elastomer composition

    JP2000007858A

  • Adhesive thermoplastic elastomer composition, composite molded article of the same and method for producing the same

    JP2006052277A

  • Polyurethane foam and water-stopping gasket

    JP2007016070A

  • Thermoplastic elastomer composition for sealant, molding material, and capacitor

    JP2008024882A